Development and Temperature-induced Expression of a HSP90 Gene Lacking Introns in Cotesia chilonis (Hymenoptera: Braconidae). (3rd September 2022) - Li, Shuan-Gan; Dong, Chuan-Lei; Zhu, Feng; Yang, Fei; Lu, Ming-Xing; Du, Yu-Zhou
Abstract: Cotesia chilonis (Munakata) is the predominant parasitic wasp of Chilo suppressalis Walker (Lepidoptera: Pyralidea), a major rice pest in China. As climate change continues to intensify, C. chilonis and C. suppressalis must adapt to the increased frequency of adverse temperatures. In this study, the novel Cchsp90-2 was isolated and characterized from C. chilonis . The full-length Cchsp90-2 cDNA was 2689 bp and encoded 728 amino acids with an isoelectric point of 4.93. Cchsp90-2 encodes three heat shock protein 90 (HSP90) family signatures, and the alignment of genomic and cDNA sequences revealed that Cchsp90-2 does not contain introns. Real-time quantitative PCR revealed that Cchsp90-2 was induced in eggs and adults; however, larvae and pupae showed no significant differences in Cchsp90-2 expression levels. Cchsp90-2 was induced at both high and low temperatures, with very high expression levels after a 2-h exposure to 33°C or −13°C. This study provides insight into the mechanistic basis of thermal tolerance in C. chilonis and has implications for deploying this wasp to control C. suppressalis .